EFFECT OF WAREHOUSE MANAGEMENT SYSTEMS ON SUPPLY CHAIN PERFORMANCE OF FAST-MOVING CONSUMER GOODS MANUFACTURERS IN KENYA - Muhalia, Eric Jepherson; Ngugi, Patrick Karanja; Moronge, Makori (International Journal of Supply Chain Management, 2021)
Purpose: The purpose of this study was to establish the effect of warehouse management systems on supply chain performance of fast-moving consumer goods manufacturers in Kenya Methodology: The study adopted descriptive research design. The unit of observation was the operations manager of the 51 FMCG manufacturers located in Nairobi. The sampling frame of the current study consisted of operations managers in the manufacturers of the FMCGs in Nairobi. The study used the census method to select 51 manufacturers of the FMCGs in Nairobi, thus the sample of the study was 51 respondents. Primary data was used in the study. The study used questionnaires to collect data. Mixed methods technique of analyzing data was used where both descriptive and inferential analysis were used. The data collected from the field was analyzed using SPSS 23 program. The questionnaires were referenced and the items in them coded for easier data entry. The presentation of the findings was done using tables. Results: The study found that warehouse management systems positively and significantly influences Supply chain performance of FMCG in Kenya. The study found that the respondents were in agreement that warehouse management system helps to reduce picking errors; warehouse management system facilities the maximum use of storage space; warehouse management system helps to optimize stock control; warehouse management system improves work productivity; and that warehouse management system guide workers through risk assessments and flag up warehouse safety requirements. Unique contribution to theory, practice and policy: The study recommended that when warehouse management systems are improved, supply chain performance of the company improves as well. The study recommends management of the company to ensure they remain informed on the changes in the market to ensure that their warehouse management system is up-to-date and therefore avoid process redundancy and inaccurate inventories. There is a need to use strategic approach in practices of managing logistics by embracing modernized technology and training of employees on the use of the same.